Mac OS 9 - Langer, Maria (Visual quickstart guide., 2000)
A guide to the updated Mac operating system demonstrates application basics, file management, networking, working with PC files, security and multiple users, customizing the interface, and troubleshooting, and includes a section on Mac's iBook.